FORMULATION AND EVALUATION OF AMPICILLIN TRIHYDRATE AND ACRYLIC RESINS CO-PRECIPITATE INTO A SOLID DOSAGE FORM - I. V., Emenike; S. Y, Timothy; Midala, T. A. S.; Oduola, A. R.; Musa, H. (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2016)
The aim of this study is to formulate and evaluate the ampicillin trihydrate and acrylic resins co-precipitate as a sustained release solid dosage form. Three ampicillin tablet formulations designated T-I, T-II and T-III containing pure drug, drug/Eudragit(R) (1:1) and drug/Eudragit(R) (2:1) coprecipitates respectively were prepared in order to produce tablets with satisfactory quality suitable for comparative studies. Evaluation of compressed tablets was carried out and the results compared with standards given in the official books. Uniformity of content and dissolution rate studies were the parameters evaluated. A product is considered satisfactory when the evaluation results of the product are in conformity with the standards given in the official books. The uniformity of content was within (- 3.9% to +0.4% for T-I),(-6.1% to +0% for T-11) and (-9% to +0.4% for T-111) formulations respectively. These results are within the official acceptable specifications of ±15% for nine (9) tablets, with none exceeding ±25%. About 87%, 35.5% and 52.0% of drug dissolution were attained after one hour from formulations T-I, T-II and T-III respectively. Formulations T-II therefore shows a significant retardation in the drug release rate. The mechanism of drug release from these formulations (T-II and T-III) is by erosion. It appears that drug release profiles from T-II and T-III are closer to first-order kinetics than zero-order kinetics; this is due to gradual decrease in the tablet surface area due to erosion. The results of this study have shown a considerable influence of EudragitRS(R) on the retardation of the release rate of ampicillin trihydrate in the designed tablet formulation in a given set of in vitro study.